2015
DOI: 10.1002/imhj.21548
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mind‐mindedness: Relations With Maternal–fetal Attachment and Stability in the First Two Years of Life: Findings From an Australian Prospective Study

Abstract: Mind-mindedness captures a caregiver's attunement to his or her infant's mental states, and the tendency to interpret behavior as resulting from these mental states. The construct is assessed through analysis of maternal language during interaction or from mothers' use of mental state words when invited to describe their child. This study examined whether maternal-fetal attachment predicted maternal mind-mindedness, whether there was continuity in mind-mindedness over the first 2 postnatal years, and concordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 48 publications
5
38
0
3
Order By: Relevance
“…Few studies have examined associations between sensitivity and non-attuned comments, with evidence limited to this single sample. Most studies do not report on nonattuned comments at all, as they are very infrequent and most mothers do not make any (Bernier, McMahon, & Perrier, 2017;Easterbrooks, Crossman, Caruso, Raskin, & Miranda-Julian, 2017;Licata et al, 2014;McMahon, Camberis, Berry, & Gibson, 2016). Meins et al (2012) in the study cited above reported an average proportional score for non-attuned comments of just 1.58% which is consistent with other research in community samples.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Few studies have examined associations between sensitivity and non-attuned comments, with evidence limited to this single sample. Most studies do not report on nonattuned comments at all, as they are very infrequent and most mothers do not make any (Bernier, McMahon, & Perrier, 2017;Easterbrooks, Crossman, Caruso, Raskin, & Miranda-Julian, 2017;Licata et al, 2014;McMahon, Camberis, Berry, & Gibson, 2016). Meins et al (2012) in the study cited above reported an average proportional score for non-attuned comments of just 1.58% which is consistent with other research in community samples.…”
supporting
confidence: 84%
“…Few studies have examined associations between sensitivity and non‐attuned comments, with evidence limited to this single sample. Most studies do not report on non‐attuned comments at all, as they are very infrequent and most mothers do not make any (Bernier, McMahon, & Perrier, ; Easterbrooks, Crossman, Caruso, Raskin, & Miranda‐Julian, ; Licata et al., ; McMahon, Camberis, Berry, & Gibson, ). Meins et al.…”
Section: Appropriate and Non‐attuned Mind‐related Comments And Maternmentioning
confidence: 99%
“…However, this should not be taken to mean that there is an association between maternal SES and early mind‐mindedness; in fact, the evidence on this link is somewhat equivocal. For example, Meins, Fernyhough, Arnott, Turner, and Leekam (); Bigelow, Power, Bulmer, and Gerrior (); and McMahon, Camberis, Berry, and Gibson () reported no association between SES and mothers' appropriate mind‐related comments, whereas Bernier et al. () and Laranjo and Bernier () reported small to medium positive correlations between SES and appropriate comments ( r s of .20 and .26, respectively).…”
mentioning
confidence: 99%
“…Previous research involving biological families has suggested that mindmindedness is relatively stable over time (Illingworth, MacLean, & Wiggs, 2016;Kirk et al, 2015;Meins, Fernyhough, Arnott, Leekam, & Turner, 2001;Meins et al, 2003;McMahon, Camberis, Berry, & Gibson, 2016). But this stability has been observed only within early childhood, and no study has investigated whether mind-mindedness changes in concert with fluctuations in the quality of the relationship.…”
Section: Discussionmentioning
confidence: 99%